A condição financeira governamental e sua influência na transparência da gestão pública municipal - Nobre, Carla Janaina Ferreira (2017)
This study aimed to verify the relationship between the financial condition and the level of fiscal transparency of the municipalities of Paraíba. The theoretical support that underpinned this research is based on theories of fiscal federalism, the management of impressions and legitimacy, as well as the contribution of empirical studies. Thus, allowing to raise the hypothesis that the better the financial condition, the better the transparency indexes in the municipalities. The model of Brown (1993) was used to measure the financial condition of the municipal governments and the transparency index was established by the Court of Accounts of the State of Paraíba. In addition to the use of the fine control variable, which is applied by the TCE / PB in detriment of irregularities caused by the managements. According to the statistical model presented, in which the dependent variable is transparency, and regressed through panel Tobit, it was found that the financial condition and the fine are determining factors of transparency, thus, proving that as the Financial condition improves, transparency in disclosure increases, confirming the hypothesis of the survey, with a significance of 1%. In addition, the marginal effects of the variables showed a strong link between the fine and the financial condition with transparency. Of the regressive models used, that is, of the variable transparency, with its total score, or in its 3 aspects (usability, historical series and content), we also observed a significant relation with the financial condition and the fine, with the exception of usability. Robustness tests, to verify if the presence of the fine actually affects the transparency indexes, were made and proved this question. The findings of this investigation corroborated with Zuccolotto and Teixeira (2014), Cruz et al. (2010), De Paiva Ribeiro and Zuccolotto (2014). An analysis of the financial condition of the municipalities of Paraíba each year (2013 to 2015) was carried out, and in each group of municipalities by the population number, confirming the evidence of Dal Vesco et al. (2014). The research results contributed to the theoretical framework and empirical studies on financial condition and transparency, serving as support for public management in the administration of public resources and disclosure of transparent information.